Production of the 2,5-Furandicarboxylic Acid Bio-Monomer From 5-Hydroxymethylfurfural Over a Molybdenum-Vanadium Oxide Catalyst - Liu, Jian; Wen, Sha; Wang, Fei; Zhu, Xiaoting; Zeng, Zhijuan; Yin, Dulin (Frontiers in Chemistry, 2022)
2,5-Furandicarboxylic acid (FDCA) is an important bio-monomer that can potentially replace terephthalic acid to synthesize degradable polyesters. Efficient selective oxidation of biomass-based 5-hydroxymethylfurfural (HMF) to FDCA has been a significant but challenging work in the past decades. In this study, a novel molybdenum-vanadium oxide (Mo-V-O) catalyst was prepared by a simple method and showed excellent catalytic activity for converting HMF to FDCA. A high FDCA selectivity of 94.5% and 98.2% conversion of HMF were achieved under the optimal conditions with tert-butyl hydroperoxide as the oxidant. FT-IR, SEM, XRD and TG were applied to investigate the properties of Mo-V-O catalyst. After fitting experimental data with the first-order kinetics equation, the evaluated apparent activation energies of HMF oxidation were obtained. The experimental design and study were carried out by response surface methodology (RSM) to test the effects of reaction conditions on the catalytic process.